Economic benefits from production of biogas based on animal waste within energy co-operatives in Ukraine - Kurbatova, Tetiana (International Journal of Sustainable Energy Planning and Management, 2018)
The research deals with problems of animal waste potential usage in order to produce biogas for energy generation in Ukraine. Although there are favorable conditions to develop biogas sector based on animal waste, the share energy, produced from it, is extremely low. The paper analyzes energy potential of agricultural biomass in Ukraine, economic tools, aimed at stimulating electricity generation from biogas based on animal waste, the results of their impact on biogas plants deployment. Among a number of barriers, which inhibit the development of this sector in Ukraine, the main ones are the need for significant initial investments to construct profitable biogas plants and a large amount of raw materials for their uninterrupted operation. Given the fact that 48.2% of farm animals are concentrated in small-scale farms and households, which cannot individually implement biogas projects, it is proposed to combine their financial and raw material resources within energy co-operatives. Economic benefits, which may be gained by small-scale farms within energy co-operative through the sale of electricity, generated from biogas, by feed-in tariff are calculated. It is discussed that in addition to economic benefits for small-scale farms owners, realization of the co-operative model in the bio-energy sector will let to obtain a number of ecological and social benefits both for territorial communities, and the state as a whole.